2016
DOI: 10.1007/s00056-015-0007-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural color changes in permanent enamel of patients with cleft lip and palate: a case–control study

Abstract: The higher prevalence of enamel color changes in the CLP group (more than threefold compared to the control group) was not related to previous orthodontic treatments; however, systemic fluoridation (table salt and tablets) constituted a risk factor for the enamel color changes seen in the CLP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Studies grouping DAs (e.g., combining peg-shaped incisors and hypoplasia; Walker et al 2009) were excluded if the number of participants with each anomaly was not identified after checking the supplemental data files and contacting the corresponding authors. Articles that were unclear about excluding individuals with syndromic OCs were excluded if the syndromic status of the participants was not obtained after contacting the corresponding authors (Chopra et al 2014; Kulas et al 2016; Kamble et al 2017). When studies reported outcome per >1 age group or dentition (Howe et al 2015; Sundell et al 2016), each age group/dentition was included separately in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Studies grouping DAs (e.g., combining peg-shaped incisors and hypoplasia; Walker et al 2009) were excluded if the number of participants with each anomaly was not identified after checking the supplemental data files and contacting the corresponding authors. Articles that were unclear about excluding individuals with syndromic OCs were excluded if the syndromic status of the participants was not obtained after contacting the corresponding authors (Chopra et al 2014; Kulas et al 2016; Kamble et al 2017). When studies reported outcome per >1 age group or dentition (Howe et al 2015; Sundell et al 2016), each age group/dentition was included separately in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The aetiology of DDE is not entirely clear, but it has been associated with poor maternal health during pregnancy, pre‐term birth and hospitalization in the first year of life; the majority of these children would have been admitted to hospital in their first year of life for cleft repair operations. There is scant evidence as to why children born with a cleft have a high prevalence of DDE but a case control study looking at permanent teeth showed colour changes (which would include DDE, mild fluorosis, early dental caries) of enamel three times more likely in these children . There is likely upset to enamel formation in the developmental stages, and this manifests in these colour changes.…”
Section: Discussionmentioning
confidence: 99%
“…Chapple et al showed that developmental defects of enamel became more prevalent with age, with prevalence of 56% of 4-year-olds and 100% of 12-year-olds in patients with CLP ( 32 ). Kulas et al carried out a case-control study and observed enamel color changes of permanent teeth three times more often in CLP children ( 33 ). While another research showed that there was no significant difference ( P > 0.05) in the prevalence of development defects involving enamel among children with and without cleft ( 13 ).…”
Section: Mechanisms Linking Dental Caries and Clpmentioning
confidence: 99%
“…Treatment of children and adolescents with CLP needs an organized team approach to provide optimal results. Orthodontic appliances have been linked to a higher caries experience ( 33 ). Fixed orthodontic appliances (FOAs) and dental prosthesis wear before or after surgical repair of CLP patients provides blind spots and reduces the effectiveness of saliva self-cleaning function ( 49 ).…”
Section: Mechanisms Linking Dental Caries and Clpmentioning
confidence: 99%